2020
DOI: 10.4054/demres.2020.42.4
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation and ethnic marriage-squeeze in early 20th century America: A gender perspective

Abstract: BACKGROUND During the 19 th and early 20 th centuries, large waves of international immigrants, often heterogeneous in terms of age and sex structure, arrived in the United States. Within a relatively short time, many of these immigrants were assimilated. While prior studies have identified an impact of the marriage squeeze on intermarriage, the role of gender is less known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Their econometric results show that ethnic group size generally has a negative and statistically significant association with male and female intermarriage rates while the within-group sex ratio has a positive but statistically insignificant association on intermarriage rates. Weiss and Stecklov (2020) use data from the 1930 US Census of Population on the six largest emigration countries (England, Germany, Ireland, Italy, Poland, and Russia) to examine the influence of ethnic sex ratios on intermarriage. They specify two distinctly different sex ratio variables: One is the traditional within-group sex ratio for an ethnic group, while the second is an extra-group sex ratio measuring female scarcity in all other ethnic groups (p. 7).…”
Section: Review Of the Literatures On The Impact Of Sex Ratios On Mar...mentioning
confidence: 99%
See 2 more Smart Citations
“…Their econometric results show that ethnic group size generally has a negative and statistically significant association with male and female intermarriage rates while the within-group sex ratio has a positive but statistically insignificant association on intermarriage rates. Weiss and Stecklov (2020) use data from the 1930 US Census of Population on the six largest emigration countries (England, Germany, Ireland, Italy, Poland, and Russia) to examine the influence of ethnic sex ratios on intermarriage. They specify two distinctly different sex ratio variables: One is the traditional within-group sex ratio for an ethnic group, while the second is an extra-group sex ratio measuring female scarcity in all other ethnic groups (p. 7).…”
Section: Review Of the Literatures On The Impact Of Sex Ratios On Mar...mentioning
confidence: 99%
“…We compute these both within and outside of the individual's ethnic group. 21 This specification builds on Weiss and Stecklov (2020) who pioneered the use of both measures. The variable, ForeignBorn jt , is the first-generation population of marriageable age of ethnic group j in census year t. The variables M i and F i , are binary variables showing type of mixed parentage (foreign-born mother-only [M i ] or foreign-born father-only [F i ]).…”
Section: Econometric Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic literature on the marriage squeeze has shown that societal sex imbalances can promote intermarriage with other groups [23][24][25][26][27]. First generation migrant communities historically present skewed sex distributions because of male-or femaledominated flows of migration.…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…In this paper, we study the differential infant and child mortality in Madrid between 1916 and 1926, according to the birthplace of the mothers. Historical demographers have studied the integration of newcomers into growing urban populations through the lenses of intermarriage (Dribe et al 2018; Weiss and Stecklov 2020; Pagnini and Morgan 1990) and fertility (Kulu et al 2019; Moreels and Vandezande 2012; Schumacher et al 2013). The immigrant mortality paradox is also well known, describing the undermortality of international immigrants but also of rural-urban migrants because of their selection among healthier people (Kesztenbaum and Rosental 2011; Oris and Alter 2001; Puschmann et al 2016).…”
Section: Introductionmentioning
confidence: 99%